2011
DOI: 10.4084/mjhid.2011.064
|View full text |Cite
|
Sign up to set email alerts
|

How I Treat Newly Diagnosed Acute Promyelocytic Leukemia

Abstract: Acute promyelocytic leukemia (APL) represents a medical emergency with a high rate of early mortality. As a consequence, as soon as the diagnosis is suspected based upon cytologic criteria, it is necessary to start all- trans retinoic acid (ATRA) treatment without delay. For patients with newly diagnosed APL, induction therapy with ATRA plus anthracycline based chemotherapy is recommended. At present the combination of arsenic trioxide plus ATRA should be considered for patients who are not candidates for anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(59 reference statements)
0
4
0
Order By: Relevance
“… 53 Relatively high-dose anthracyclines (450–750 mg/m 2 ) used in modern chemotherapy plus ATRA regimens have proven successful to achieve high cure rates in adults and children with APL, although the high cumulative anthracycline dose was potentially associated with high risk of late cardiotoxicity. 4 , 6 , 7 , 44 Although no severe acute cardiotoxicity was observed in our first GIMEMA-AIEOP study, longer follow-up is needed to define the late cardiotoxicity of anthracycline regimens. Late subclinical cardiotoxicity was observed in 52% of the adult survivors of APL treated on the GIMEMA AIDA-0493 and-2000 protocols.…”
Section: Are There Particular Treatment Issues For Children With Apl?mentioning
confidence: 85%
See 1 more Smart Citation
“… 53 Relatively high-dose anthracyclines (450–750 mg/m 2 ) used in modern chemotherapy plus ATRA regimens have proven successful to achieve high cure rates in adults and children with APL, although the high cumulative anthracycline dose was potentially associated with high risk of late cardiotoxicity. 4 , 6 , 7 , 44 Although no severe acute cardiotoxicity was observed in our first GIMEMA-AIEOP study, longer follow-up is needed to define the late cardiotoxicity of anthracycline regimens. Late subclinical cardiotoxicity was observed in 52% of the adult survivors of APL treated on the GIMEMA AIDA-0493 and-2000 protocols.…”
Section: Are There Particular Treatment Issues For Children With Apl?mentioning
confidence: 85%
“…As suggested by Van Dalen et al, the risk of developing clinical heart failure is dose-dependent, increasing from 0% for 150 mg/m 2 of cumulative anthracycline dose, up to 14.3% for doses of 600 mg/m 2 53. Relatively high-dose anthracyclines (450–750 mg/m 2 ) used in modern chemotherapy plus ATRA regimens have proven successful to achieve high cure rates in adults and children with APL, although the high cumulative anthracycline dose was potentially associated with high risk of late cardiotoxicity 4,6,7,44. Although no severe acute cardiotoxicity was observed in our first GIMEMA-AIEOP study, longer follow-up is needed to define the late cardiotoxicity of anthracycline regimens.…”
Section: Are There Particular Treatment Issues For Children With Apl?mentioning
confidence: 99%
“…Anthracycline-related cardiotoxicity is also a concern106,107 as research has shown that patients treated on AIDA-based protocols developed subclinical but detectable diastolic dysfunction and regional wall motion abnormalities 106. Recognized common acute side effects associated with ATRA therapy include fever, rash, headache and pseudotumor cerebri; the latter occurs more commonly in adolescents/children and may prompt dose reduction or cessation of ATRA in severe cases 108. Long-term toxicity secondary to ATRA therapy has not been seen but requires ongoing review.…”
Section: Atra Eramentioning
confidence: 99%
“… 106 Recognized common acute side effects associated with ATRA therapy include fever, rash, headache and pseudotumor cerebri; the latter occurs more commonly in adolescents/children and may prompt dose reduction or cessation of ATRA in severe cases. 108 Long-term toxicity secondary to ATRA therapy has not been seen but requires ongoing review.…”
Section: Atra Eramentioning
confidence: 99%